Community Empowerment Through Soka Crab Cultivation in an Effort to Improve the Economy and Welfare of the Nunang Aceh Tamiang Pipeline - Maisarah; Mursyidin; Fauzi; Fakhrurrazi; Pangeran Putra Perkasa Alam Nasution (Jurnal Transparansi Publik (JTP), 2025)
This research is entitled “Community Empowerment Through Soft-Shell Crab Farming as an Effort to Improve the Economy and Welfare (A Case Study of the Sumber Rezeki and Bangka Pulo Groups in Alur Nunang Village, Banda Mulia Subdistrict, Aceh Tamiang Regency).” The study aims to understand the empowerment process carried out by the Sumber Rezeki and Bangka Pulo groups, as well as how soft-shell crab farming contributes to improving the economy and welfare of coastal communities. This study employs a qualitative descriptive method. Data were collected through observation, in-depth interviews, and documentation involving key informants, main informants, and additional informants. Data analysis consisted of data reduction, data display, and conclusion drawing. The findings show that the community empowerment process was implemented through several stages: potential identification, alternative assessment, socialization and group formation, training and knowledge transfer, collective implementation of farming activities, and institutional strengthening and evaluation. This empowerment process has successfully increased household income, expanded employment opportunities, and strengthened social solidarity among group members. The success of the program was supported by social network cooperation, assistance from the NGO KEMPRA, and the sustainable use of local ecological resources. Therefore, community empowerment through soft-shell crab farming has proven not only to improve the economic condition of coastal communities but also to build independence and ecological awareness that support socio-economic sustainability in Alur Nunang Village.